A participação da imagem midiática nos distúrbios de imagem corporal derivados dos transtornos alimentares na infância - Silva, Victória Stephanie Duarte da (2022)
The purpose of this essay is to analyze the participation of the mass media image on the child's body in body image disorders derived from eating disorders in childhood, from the point of view of professionals who deal with such cases. The proposal covers the mass media image perspective, and the concept of Female Gender, the Myth of Beauty, the Childhood and Body Image Disorders and Eating Disorders in Childhood. The methodological techniques were applied to interviews with professionals from the public and private health network who treats children with Eating Disorders. According to the analysis of the information collected, carried out after the fact, the results obtained indicate that mass media images are related to the emergence and progress of body image disorders in female children; mass media images had been identified to be conected with inception and development of body image desorders in both first and second childhood; and lower class citzens do have childhood eating disorders, but the case counting of lower class people in childhood eating disorders treatments is minuscule.